2018 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2018
DOI: 10.1109/icsme.2018.00073
|View full text |Cite
|
Sign up to set email alerts
|

Relational Database Schema Evolution: An Industrial Case Study

Abstract: Modern relational database management systems provide advanced features allowing, for example, to include behaviour directly inside the database (stored procedures). These features raise new difficulties when a database needs to evolve (e.g. adding a new table). To get a better understanding of these difficulties, we recorded and studied the actions of a database architect during a complex evolution of the database at the core of a software system. From our analysis, problems faced by the database architect ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…Others were never fully propagated. We argue that, according to what we observed in previous research [4] and the research made in this article, propagating structural change to behavior entities of the database is a hard task as well.…”
Section: Related Worksupporting
confidence: 68%
See 2 more Smart Citations
“…Others were never fully propagated. We argue that, according to what we observed in previous research [4] and the research made in this article, propagating structural change to behavior entities of the database is a hard task as well.…”
Section: Related Worksupporting
confidence: 68%
“…Before each migration, he prepares a road map containing, in natural language, the list of operators initially planned for the migration. We observed that these road maps are not complete or accurate [4]. Following a long manual process, the architect writes a SQL patch (i.e., a text file containing queries) to migrate from one version of the database to the next one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the extracted migration files using the sqlmigrate tool, provided by the Django framework itself. 3 This tool processes a given migration file and produces the exact DDL commands intended to be executed in the database schema.…”
Section: Concept Operationalizationmentioning
confidence: 99%
“…Despite their potential negative impact on important quality attributes, blocking operations have not yet been empirically investigated in the context of software evolution. So far, empirical studies have investigated the evolution of the database schema alone [2,3,12] or the joint evolution of the database and application source code [7,8]. But none of these works have investigated the occurrence of blocking operations during database schema evolution.…”
Section: Introductionmentioning
confidence: 99%